Free to believe rethinking freedom of conscience and religion in Canada - Waldron, Mary Anne, 1948- (Toronto [Ont.] : University of Toronto Press, 2013)
Free to Believe investigates the protection for freedom of conscience and religion -- the first of the "fundamental freedoms" listed in the Canadian Charter of Rights and Freedoms -- and its interpretation in the courts.
Introduction. How freedom of conscience and religion are protected and why it matters -- Early cases : getting off on the wrong foot -- Culture wars : majority versus minority values -- When religion and politics intertwine -- Human rights : a zero sum game? -- Conflicting rights : a balancing act? -- Freedom of conscience : the forgotten human right -- Can we change? : (And why we should).
Includes bibliographical references (p. [243]-284) and index.
Keywords: Liberty of conscience -- Canada -- Cases; Freedom of religion -- Canada -- Cases; LAW / Constitutional; LAW / Public; Electronic books